2022
DOI: 10.1101/2022.01.14.476414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extant Sequence Reconstruction: The accuracy of ancestral sequence reconstructions evaluated by extant sequence cross-validation

Abstract: Ancestral sequence reconstruction (ASR) has become widely used to analyze the properties of ancient biomolecules and to elucidate the mechanisms of molecular evolution. By recapitulating the structural, mechanistic, and functional changes of proteins during their evolution, ASR has been able to address many fundamental and challenging evolutionary questions where more traditional methods have failed. Despite the tangible successes of ASR, the accuracy of its reconstructions is currently unknown, because it i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Across all protein families tested, AP-LASR achieved improved or comparable eLnP scores compared to FireProt ASR . Note that a greater (less negative) eLnP number represents greater confidence[33]. This metric was chosen for two reasons: it can compare ASR outputs from various software or models in an unbiased way and it offers assessments even in the absence of definitive ‘correct’ ancestors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all protein families tested, AP-LASR achieved improved or comparable eLnP scores compared to FireProt ASR . Note that a greater (less negative) eLnP number represents greater confidence[33]. This metric was chosen for two reasons: it can compare ASR outputs from various software or models in an unbiased way and it offers assessments even in the absence of definitive ‘correct’ ancestors.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of the final reconstructed ancestry is quantified using the eLnP metric, as proposed by Sennett and Theobald (Equation 1)[33]. eLnP quantifies the overall uncertainty in the reconstructed sequence distribution and was used as our benchmark to evaluate the efficacy of AP-LASR against well-established software such as FireProt ASR .…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that the number of correct residues is linearly proportional to the average sequence probability. 18 Regardless, if selecting the SMP state does indeed result in the fewest sequence errors then we should also expect that it’s physicochemical properties when resurrected is most like the true ancestral protein. However, the concern remains that systematically selecting the most probable residue at each site will impart a property bias in the SMP sequence relative to the true sequence.…”
Section: Introductionmentioning
confidence: 99%